Improving tetanus prophylaxis in the emergency department: a prospective, double-blind cost-effectiveness study. Issue 9 (21st August 2007) - Stubbe, Muriel; Mortelmans, Luc J M; Desruelles, Didier; Swinnen, Rohnny; Vranckx, Marc; Brasseur, Edmond; Lheureux, Philippe E
Abstract : Background: The choice of tetanus prophylaxis for patients with wounds depends on obtaining their vaccination history, which has been demonstrated to be unreliable. Use of a rapid immunoassay (Tétanos Quick Stick, the TQS), combined with knowledge of certain demographic characteristics, may improve the evaluation of tetanus immunity and thus help to avoid inadequate prophylactic measures and reduce costs. Objectives: To evaluate the contribution of the TQS in the choice of tetanus prophylaxis and to perform a cost-effectiveness analysis. The final aim was to define the place of the TQS in a modified algorithm for assessment of tetanus immunity in the emergency department. Method: In this Belgian prospective, double-blind, multicentre study, 611 adult patients with a wound were included; 498 (81.5%) records were valid. The TQS test was performed by a nurse before the vaccination history was taken and the choice of prophylaxis was made, using the official algorithm (Belgian Superior Health Council), by a doctor who was unaware of the TQS result. Results: The prevalence of protective anti-tetanus immunity was 74.1%. Immunity was lower in older patients and in female patients. The TQS was a cost-effective tool for patients presenting with a tetanus-prone wound and considered from the vaccination history to be unprotected. Use of the TQS would have improved management in 56.9% (95% CI 47.7% to 65.7%) of patients by avoiding unnecessary treatments, leading to a reduction in the mean cost per patient (€10.58/patient with the TQS versus €11.34/patient without). The benefits of the TQS use were significantly greater in patients <61 years old: unnecessary treatment would have been avoided in 76.9% (95% CI 65.8% to 85.4%) of cases and the mean cost per patient reduced to €8.31. Conclusion: In selected patients, the TQS is a cost-effective tool to evaluate tetanus immunity. An algorithm is proposed for ED assessment of tetanus immunity integrating age and the TQS result.